AWARENESS ABOUT TB AND HIV / AIDS – ONE OF THE MEANS OF PREVENTION - Вородюхіна, А.К.; Ярешко, А.Г.; Boiko, M.; Haran, O. (World of Medicine and Biology, 2014)
To determine the role of awareness in the prevalence of diseases such as tuberculosis and HIV / AIDS, we surveyed in Poltava and Poltava region 2104 different age, sex, social status, place of residence, education, attitudes towards a healthy lifestyle respondents. These results indicate that the majority of respondents are not sufficiently aware of the incidence of tuberculosis, routes of transmission of HIV / AIDS and factors preventing the development of these diseases.
Keywords: Tuberculosis; HIV; AIDs; respondents; prevention